Prevalence of Entamoeba histolytica, Giardia lamblia, and Cryptosporidium spp. in Libya: 2000–2015. Issue 1 (1st January 2016) - Ghenghesh, Khalifa Sifaw; Ghanghish, Khaled; BenDarif, Elloulu T.; Shembesh, Khaled; Franka, Ezzadin
Abstract : Introduction: The intestinal protozoa Entamoeba histolytica, Giardia lamblia, and Cryptosporidium spp. are the causative agents of giardiasis, amebiasis, and cryptosporidiosis, respectively. Adequate knowledge of the geographical distribution of parasites and the demographic variables that influence their prevalence is important for effective control of infection in at-risk populations. Methods: The data were obtained by an English language literature search of Medline and PubMed for papers using the search terms 'intestinal parasites and Libya, G. lamblia and Libya, E. histolytica and Libya and Cryptosporidium and Libya' for the period 2000–2015. Results: The data obtained for the period 2000–2015 showed prevalence rates of 0.8–36.6% (mean 19.9%) for E. histolytica/dispar, 1.2–18.2% (mean 4.6%) for G. lamblia and 0.9–13% (mean 3.4%) for Cryptosporidium spp. among individuals in Libya with gastroenteritis (GE). On the other hand, prevalence rates of 0.8–16.3% (mean 8.3%), 1.8–28.8% (mean 4.8%), and 1.0–2.5% (mean=2.4), respectively, were observed for individuals without GE. The mean prevalence rate of E. histolytica / dispar was significantly higher among individuals with GE compared with those without GE ( p <0.0000001, OR=2.74). No significant difference in prevalence rate of the three organisms was found according to gender, but most of infections were observed in children aged 10 years or younger. Conclusion: The reviewed data suggest that E. histolytica, G. lamblia, and Cryptosporidium spp. may play a minor role in GE in Libya. The observed high prevalence rates of E. histolytica / dispar reported from Libya could be due mainly to the non-pathogenic E. dispar and E. moshkovskii . However, more studies are needed in the future using E. histolytica -specific enzyme immunoassays and/or molecular methods to confirm this observation.